A THINKING PIECE. THE ROLE OF LANGUAGE IN EDUCATION FOR PEACE - ETEMADIBOUSHERI, SANAZ (Society Register, 2019)
Iran is a country of great ethnic diversity. Although the official language of the country is Farsi, more than 8 other languages and hundreds of dialects are spoken throughout the country. This great ethnic diversity has led to emergence and growth of different cultures and religions (both official and non-official). This great diversity has potential for cultural growth and development. In recent years, many non-governmental organizations have made great efforts to teach children peace in different ways. The biggest motivation for these trainings are: to end misbelieves toward education, and professing to equal citizenship rights for all the ethnic groups. In the past 20 years, the issue of the right to equal education has been a hot topic of discussion in most non-governmental children’s researches. This refers to the promotion of peace culture, by peace-based educational programs for all age groups, from the beginning pre-school education stages. A group of active consultants and educational planners did a lot of work in this way. They held lots of workshops and meetings, and achieved successful programs with positive results.